POSITION OF PRADANA IN NYEBURIN MARRIAGE REVIEWED FROM THE LAW OF BALI INDIGENOUS HERITAGE IN BANJAR KUTUH DESA SAYAN KECAMATAN UBUD KABUPATEN GIANYAR - Ni Kadek Sinta Dewi; I Nyoman Putu Budiartha (Scopus ID: 57202765630); I Nyoman Sujana (NOTARIIL Jurnal Kenotariatan, 2020)
The aims of this study are to know the Nyeburin Marriage Inheritance System in Banjar Kutuh, Sayan Village, Ubud District, Gianyar Regency women as Purusa or nyentana men as Pradana if their inheritance is in the form of land assets and to know the position of social social status of men as Pradana in Nyeburin Marriage in indigenous communities in the Village of Sayan Banjar Kutuh, Ubud District, Gianyar Regency. This method uses Empirical legal research. Using the statutory approach, case approach, and conceptual approach. Sources of data are sourced from primary data (field research) and secondary data (library research). Data collection techniques consisted of interview techniques, document study techniques, and literature study techniques. The data collected was analyzed descriptive qualitatively. The author uses the theory of justice, the theory of legal certainty, the theory of reception in complex u. Based on the results of the study it was found that the inheritance of nyeburin marriage in Banjar village is still strong in women because of their status as Purusa and their social social status is different if the work of a person who becomes a pradana, for example, a doctor may look higher. The conclusion is that a woman still has the right to inherit because as a purusa and if the inheritance in the form of land remains the right of the woman and in social status remains the head of the household in the community remains the same except for work that makes their social status different.